SIMILARITIES AND DIFFERENCES OF THE CATEGORY OF VOICE IN ENGLISH AND UZBEK LANGUAGES - Azimov Sardorbek; Aziz Mukhammadiev (Journal of new century innovations, 2024)
Annotation: This article explores the voice category in English and Uzbek languages, focusing on similarities and differences in the use of active, passive, and middle voices. Through detailed analysis, it examines the formation of voice, its grammatical features, and its significance in linguistic structures. Examples and constructions are used to illustrate distinctive characteristics of the voice category, highlighting structural variations and similarities between the two languages.